Research of dynamics of transmission coefficient of multimode optical fiber from time of the crushing load at temperature -600C - Ospanova, N.A.; Zhetpisbaeva, A.T.; Kulakaeva, A.E. (Recent Contributions to Physics, 2015)
In this article we investigated ability of the transmission signal in multimode optical fiber, at influence on it crushing force at different operating temperatures. Research was conducted on the basis of the experimental installation, collected as circuit for measure of duration of radiation impulse from temperature in multimode optical fiber. The attenuation coefficients of multimode optical fibers were measured the same load and different temperature conditions after 6 days of the test. Different temperature condition, in particular, to allows estimate suitability of multimode optical fiber for use in different climatic conditions.
Keywords: multimode optical fiber, the attenuation coefficients, crushing force, temperature, fiber optical cable